PENGARUH PENGGUNAAN KOPLING MOTOR TOSSA 200 PADA MESIN MOTOR HONDA MEGAPRO TERHADAP DAYA DAN TORSI - Dwi Kurniawan, Ari; Budiyono, Budiyono; Prasetyo, Imam (Surya Teknika : Jurnal Ilmiah Teknik Mesin, 2022)
From various sources of problems with the Honda Megapro motorcycle engine when using the original Honda Megapro clutch, many say that the engine performance is not optimal, and from several sources suggest that to overcome these problems one of them is to replace the clutch using a Tossa 200 clutch. will try to replace the Honda Megapro clutch with a Tossa 200 clutch to prove the story among motorcycle children who tells that replacing a Honda Megparo clutch with a Tossa 200 clutch can affect engine performance, namely power and torque, the purpose of this study is to determine the difference between power and torque before and after After using the coupling, this test method is carried out using a dynotest tool for data collection. The power and torque produced on the Honda Megapro engine using the Megapro clutch is a maximum power of 19.2 hp with an engine speed of 10250 rpm and a maximum torque of 15.42 Nm at 6500 rpm while using the Tossa 200 clutch produces a maximum power of 21.8 The hp at the engine speed of 10750 Rpm and the maximum torque of 15.96 Nm at the engine speed of 9500 Rpm, the increase in power and torque in the Tossa 200 clutch is due to the components in the Tossa 200 clutch having 6 clutch pads, 6 clutch springs and 5 clutch plates so that the clutch is gripped. the clutch becomes stronger and minimizes the occurrence of slippage so that the clutch works optimally.Keywords: Tossa 200 clutch, Honda Megapro clutch, power, torque, daynote